POTRET PERILAKU HIDUP BERSIH DAN SEHAT MASYARAKAT PAKUMBULAN BUARAN KABUPATEN PEKALONGAN - Nor Istiqomah (Universitas Pekalongan, 2015)
Clean and Healthy Behavior must be intensified in accordance with the Regulation of the Minister of Health RI.No.2269 / Menkes / Per / XI / 2011 as an effort to control the spread of infectious diseases based environmental sanitation. Pakumbulan Subdistrict Buaran village is prone to sanitation because of impassable river as a dumping ground for household and industrial waste in the vicinity. This research will describe the behavior of clean and healthy village residents Pakumbulan Subdistrict Buaran related to 5 indicators: use of clean water, hand washing with soap and water, using latrines healthy, dispose of waste in place, and a shower 2 times a day.Methods: The study using observative analytic cross sectional approach. The data used were from questionaire and observation (ceck list). A total of 220 households or 10% of the total population Pakumbulan households in the sample in this study. The analysis was descriptive (frequency) and inferential (chi square) using SPSS 16.0.Results: Hygienic behavior and healthy citizens Pakumbulan Subdistrict Buaran still lacking. Some means is sufficient ownership of the means of water related (55.5%) and healthy latrines (46.4%), but not many people have had their own trash. This makes the behavior of littering, especially the river is still much to do (86.4%). Factors presence of the facilities (enabling factor) is not the only thing that affects the formation of behavior, evidenced PHBs still do despite the generally inadequate facilities (p = 0.233). But more detail, absence of trash 3.7 times the impact on residents littering (p = 0.001; OR 3.7; CI95% from 1.676 to 8.355).Conclusions: Residents Pakumbulan Subdistrict Buaran have a clean and healthy living behavior well, related to the use of clean water and healthy latrines. But people have a bad habit to throw litter into the river.Suggestions. Necessary cooperation and coordination between the public and the government to improve the knowledge, willingness, ability, and self-reliance of society to a clean and healthy life behavior. Keywords: clean and healthy behaviors (PHBS), trash, latrines, clean water